Monitoring chronic physical stress using biomarkers, performance protocols and mathematical functions to identify physiological adaptations in rats - de Araujo, Gustavo Gomes; Papoti, Marcelo; de Barros Manchado-Gobatto, Fúlvia; de Mello, Maria Alice Rostom [UNESP]; Gobatto, Claudio Alexandre (SAGE Publications, 2013)
This study was undertaken to characterize the effects of monotonous training at lactate minimum (LM) intensity on aerobic and anaerobic performances; glycogen concentrationsin the soleus muscle, the gastrocnemius muscle and the liver; and creatine kinase (CK), free fatty acids and glucose concentrations in rats. The rats were separated into trained (n =10), baseline (n = 10) and sedentary (n=10) groups. The trained group was submitted to the following: 60 min/day, 6 day/week and intensity equivalent to LM during the 12-week training period. The training volume was reduced after four weeks according to a sigmoid function. The total CK (U/L) increased in the trained group after 12 weeks (742.0±158.5) in comparison with the baseline (319.6±40.2) and the sedentary (261.6+42.2) groups. Free fatty acids and glycogen stores (liver, soleus muscle and gastrocnemius muscle) increased after 12 weeks of monotonous training but aerobic and anaerobic performances were unchanged in relation to the sedentary group. The monotonous training at LM increased the level of energy substrates, unchanged aerobic performance, reduced anaerobic capacity and increased the serum CK concentration; however, the rats did not achieve the predicted training volume.
Keywords: Animal us; Exercise; Glycogen; Performance; Sigmoid fit; creatine kinase; fatty acid; glucose; glycogen; lactic acid; adaptation; aerobic exercise; anaerobic capacity; anaerobic exercise; animal experiment; animal tissue; controlled study; creatine kinase blood level; fatty acid blood level; gastrocnemius muscle; glucose blood level; glycogen liver level; glycogen muscle level; male; nonhuman; physical stress; rat; sedentary lifestyle; sigmoid; soleus muscle; Adaptation, Physiological; Animal Welfare; Animals; Biological Markers; Creatine Kinase; Fatty Acids, Nonesterified; Glucose; Liver; Muscle, Skeletal; Physical Exertion; Rats; Rats, Wistar; Stress, Physiological